2D.07: NON-INVASIVE CORONARY FLOW RESERVE MEASUREMENTS IN MICE. (June 2015) - Di Lascio, N.; Lenzarini, F.; Stea, F.; Kusmic, C.; Faita, F.
Abstract : Objective: Coronary flow reserve (CFR) is a predictor of coronary artery disease. Inhalation of high concentration of the anaesthetic isoflurane (ISO) represents a non-invasive method to induce coronary vasodilation in mice avoiding intravenous adenosine infusion. However, not consistent protocols, especially concerning the time courses of the anesthesia administration, are reported. Aim of this work was to study the correct time course of coronary artery vasodilation. Design and method: Non-invasive 40 MHz Doppler ultrasound (VEVO2100, VisualSonics) was used to measure left coronary flow velocity at baseline (B, ISO1%) and at hyperemia (H, ISO2.5%). For six adult male mice (strain C57BL6, 6 months), isoflurane concentration was maintained at 1% for a 6-min period and then increased to 2.5% for the further 30 minutes. PW-Doppler images were acquired every two minutes and Velocity Time Integral (VTI) values were calculated for each time point providing VTI-time curves. Two mathematical models (sigmoid and exponential) were used to fit the data and the model providing the best fitting was used to calculate the mean time needed to reach the 90% of the plateau value (TT90). The obtained TT90 value was used to identify the duration of the high-isoflurane inhalation phase and the experiment was then repeated in ten mice (same strain and age) using the new time duration. CFR measurements (calculated as VTI(H)/VTI(B)) obtained in these conditions (CFRnew) were compared with those measured using a hyperemia duration as found in literature (approximately 4 minutes) (CFR4 min). Results: The fitting with the sigmoid model provided a lower total Absolute-Sum-of-Squares value than the exponential model (211.6 mm 2 vs 405.1 mm 2 ). The sigmoid model provided a TT90 measurements equal to 17.4 ± 6.9 minutes. Accordingly, the time point for the maximal flow was then fixed to 20.5 minutes (14 minutes of ISO2.5% after 6 minutes of ISO1%). CFR4 min values (2.10 ± 0.57) amounted to the 78.1% of CFRnew (2.8 ± 0.87) and the Bland-Altman analysis provided a significant bias of 0.69. Conclusions: These data suggest that short hyperemia durations cause a CFR underestimation; moreover, these results might be useful for the optimization of a standardized protocol for the non-invasive CFR evaluation in mice.